The Urgency of Reforming the Death Penalty Policy for Narcotics Distributors Post the Constitutional Court Decision Number 2-3/PUU-V/2007 - Apriyanti, R.A. Indah (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2023)
The most questioned severe punishment that can be given for someone is death penalty as with death penalty someone’s existence can be vanished and it is irrevokeable. Since there is no way for turning back the time and brings the life of the person that has already executed. With the establishment of death penalty, Article 28J Paragraph (1) of the 1945 Constitution and Article 29 Paragraph (2) of the Universal Declaration of Human Rights cannot be enforced. Basic Rights directly bind the three areas of state power to obey and respect them. The application of death penalty for narcotics dealers in Indonesia is not only limited to producing legal products, but the implementation of these laws also imposed by the state or the Indonesian government. The issue of whether or not the death penalty is appropriate remains and continues in Indonesia. Nevertheless, The Constitutional Court of the Republic of Indonesia in its decision Number 2—3/PUU-V/2007stated that death penalty is not against Article 28A and Article 28I 1945 Constitution. Hence, the act of distributing narcotics has also violated the human rights of many people in a nation because it can have a devastating impact on future generations of youth. This Normative legal research will be focus on:1. Whether the constitutional interpretation regarding the death policy for narcotics dealers in the Constitutional Court Decision Number 2—3/PUU-V/2007 according to the review of non-derogable rights?2. The need to reforms towards the death penalty policy for narcotics dealers in Indonesia?